Isocyanate cyclotrimerization and cyclopolymerization reaction catalysis used in polyurethane production technologies - Samborska-Skowron, R.; Balas, A. (Polimery, 2022)
Mechanism of action of various catalysts, used in the process of isocyanates cyclotrimerization, is presented in the review. The activities of the catalysts (among others industrial ones) hve been compared. Especially the catalysts such as tertiary amines, metaloorganic compounds and alkali metal carboxylates were discussed in details.